Correlational Study of Mental Health and Achievement Among University Students - Zulfa Nailufar, Eva; ‎ , Hafniza; Qusnul Khotimah, Andira; Aldrik Paembona, Brian (KnE Social Sciences, 2024)
Mental health is a state of mental well-being that enables individuals to cope with life pressures, realize their capabilities, learn effectively, work proficiently, and contribute to their communities. According to UNICEF Indonesia, several conditions that affect a person’s mental health, including anxiety, depression, panic, and stress. Data shows that 1 out of 3 Indonesian teenagers experience mental health issues. These issues have spurred the present research to analyze the correlation between students’ mental health and their academic performance on campus. This study focuses on examining the correlation between mental health and the grade point average (GPA) of accounting students at the Jakarta State Polytechnic (PNJ). The research used a combination of eXtreme Gradient Boosting (XGBoost) and Shapley Additive Explanations (SHAP). This approach facilitates the analysis of the correlation between mental health and GPA among students at PNJ. In addition to its research sample, this methodology also constitutes an innovative aspect of the study. Based on the research conducted, the correlation between mental health indicators such as stress, anxiety, and depression and a decline in students’ GPA is found to be low. However, in extreme cases, feelings of anxiety and stress exhibit a negative correlation with GPA reduction in students. Keywords: GPA, mental health, XGBoost, shap, correlation